1994
DOI: 10.1016/0016-7061(94)90062-0
|View full text |Cite
|
Sign up to set email alerts
|

The origin of gypsum in Vertisols in New Caledonia determined by isotopic characteristics of sulphur

Abstract: Gypsum crystals occur in Vertisols on the west coast of New Caledonia. These soils are derived from the weathering of basic rocks that contain no gypsum. The sulphur isotopic ratio 34S/32S was used as tracer to identify the origin of the gypsum. A total of 26 measurements of 1 3~~s were made on gypsum crystals from the Vertisols and compared to those of continental sulphates and to marine gypsum in tidal flats. The S34S value of the crystals located in New Caledonian Vertisols decreases with increasing distanc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

1995
1995
2013
2013

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 24 publications
0
12
0
Order By: Relevance
“…A significant part is probably lost by evaporation into the soil air and/or used by plant roots (transpiration). Open fractures connected to the surface observed at many places may enhance evaporation (Podwojewski and Arnold, 1994). Evaporation in deeper parts of the residuum and plant transpiration are probably the only feasible processes, which may lead to the precipitation of significant amounts of gypsum in deeper parts of the residuum.…”
Section: Infiltration Rate and Flowmentioning
confidence: 97%
“…A significant part is probably lost by evaporation into the soil air and/or used by plant roots (transpiration). Open fractures connected to the surface observed at many places may enhance evaporation (Podwojewski and Arnold, 1994). Evaporation in deeper parts of the residuum and plant transpiration are probably the only feasible processes, which may lead to the precipitation of significant amounts of gypsum in deeper parts of the residuum.…”
Section: Infiltration Rate and Flowmentioning
confidence: 97%
“…Previous workers suggested that the d 18 O and dD isotopic signatures of the hydration water of gypsum can be used as a quantitative method to interpret paleoclimate (Sofer, 1978;Halas and Krouse, 1982;Dowuona et al, 1992;Khademi et al, 1997a, b;Podwojewski and Arnold, 1994). Organic matter and pollen are generally not well-preserved in arid environments.…”
Section: Introductionmentioning
confidence: 98%
“…The dominant soil processes governing gypsum formation are primarily the availability of sulfate ions and the lack of sufficient water to remove the soluble gypsum (Buck and Van Hoesen, 2002). Gypsum can accumulate in soils through four processes: (1) in situ weathering of existing parent material (Carter and Inskeep, 1988;Taimeh, 1992), (2) sulfate-enriched precipitation from an oceanic source (Podwojewski and Arnold, 1994), (3) eolian or fluvial input of gypsum or sulfate-rich sediment (Taimeh, 1992;Van Hoesen, 2000;Buck and Van Hoesen, 2002), and (4) in situ oxidation of sulfide minerals (Mermut and Arshad, 1987;Podwojewski and Arnold, 1994). The presence of gypsum in buried soils and/ or paleosols may be used to qualitatively evaluate paleo-environmental conditions; however, recent research suggests isotopic analysis of gypsum may provide more quantitative paleoclimate data.…”
Section: Introductionmentioning
confidence: 99%
“…Notably more soluble than carbonate, the formation of pedogenic gypsum is most common in arid and semiarid climates. Four potential origins for gypsum accumulation in soils have been established :(1) in situ weathering of existing parent material (Carter and Inskeep, 1988), (2) an oceanic source resulting in sulfate enriched precipitation (Podwojewski and Arnold, 1994), (3) eolian or fluvial input of gypsum or SO4 rich sediment (Taimeh, 1992;Buck and Van Hoesen, 2002), and (4) in situ oxidation of sulfate minerals (Mermut and Arshad, 1987;Podwojewski and Arnold, 1994;Toulkeridis et al, 1998). Calcium sulfate present in gypsiferous marls can be transported by superficial water (runoff, water flows and alluvial sediments) and by groundwater (Porta, 1998).…”
Section: Introductionmentioning
confidence: 99%